Role of impacted teeth in dental arch crowding - Sawas, Mohamed Ali; Arabi, Linah Essam; Jabir, Samirah Hashim; AlSaadi, Reem Nawaf; Nassir, Mohammed Ahmed Al; Alraqibah, Mohammed Abdullah; Alhazmi, Ammar Khalid; Assiry, Muad Mohammed; Albrahim, Hassan Ali; Bukhari, Hassan Shawkat; Alyousif, Mohammed Abdulmohsen (International Journal Of Community Medicine And Public Health, 2022)
Estimates show that the prevalence of mandibular dental anterior crowding is high and might be up to 40%. The etiology of the condition has been multifactorial and evidence regarding the impact of mandibular third molars is still controversial. We discussed the potential role that impacted teeth (particularly mandibular third molars) might have in developing dental arch crowding. Evidence from different original studies and reviews regarding the impact of lower third molars on dental crowding was controversial. However, most of these studies showed that the correlation between these events was insignificant and additional studies might be needed for further validation. We have also identified many factors that can lead to dental arch crowding among the relevant studies in the literature. These factors might include general factors (including gender and age), skeletal factors (including malocclusion and growth of jaws) and dental factors (including primary tooth loss and tooth crown size), all of which were extensively discussed in the current study. Accordingly, further attention should also be paid to studying these factors.